Improving motor skills and psychosocial behaviors in children with autism spectrum disorder through an adapted judo program - Morales, Jose; Pierantozzi, Emanuela; Fukuda, David H.; Garcia, Vanessa; Guerra-Balic, Miriam; Sevilla-Sánchez, Marta; Carballeira, Eduardo (Frontiers in Psychology, 2022)
This study aimed to investigate the long-term effects of an adapted judo program on the motor skills and psychosocial abilities of children with Autism Spectrum Disorder (ASD). All participants had been diagnosed with ASD and were assessed twice, one time at the start of the intervention and again six months later, with the Test of Gross Motor Development (TGMD-3) and the Gilliam Autism Rating Scale-Third Edition (GARS-3). A one-way repeated measures MANOVA was carried out in order to evaluate these assessments, and a mediation analysis was done to determine the relationship between them. The experimental group significantly improved (p<0.05) from the pre-test to the post-test for several subtests of the TGMD-3 and the GARS-3. The study shows that participation in an adapted judo program clearly helps to improve the motor skills and psychosocial behaviors of children with ASD.